Formation of a Strategy for The Development of Agricultural Enterptise Taking into Account the Instruments of State Support ("Journal "U". Economy. Management. Finance.", 2020)
The article discusses the issues of strategic planning at the microeconomic level, taking into account measures of state support for agricultural production in the Rostov region.
Keywords: agricultural sector; region; Rostov region; state support